Utilization of finger millet in food preparations: a mini review - Poornakala , Selvaraj Jesupriya (Journal of Postharvest Technology, 2022)
In India, finger millet occupies the largest area under cultivation among the small millets. Finger millet stands unique among the cereals such as  barley, rye and oats with higher nutritional contents and has outstanding properties as a subsistence food crop. With the changes in scenario of  utilization of processed products and awareness of the consumers about the health benefits, finger millet has gained importance because of its  functional components, such as slowly digestible starch and resistant starch. Finger millet can be used in a variety of ways and is a great  substitute for other grains such as rice and other starchy grains. Processing them using traditional as well as contemporary methods for  preparation of value added and convenience products would certainly diversify their food uses. Their exploitation for preparation of ready-to-use  or ready-to-cook products would help in increasing the consumption of millets among non-millet consumers and thereby nutritional security. This  review will focus on the possibilities of utilizing finger millet as one of the basic ingredients that are being incorporated in food products and their  effect on the quality attributes of the prepared products..
Keywords: Finger millet,; nutrition enhancement; nutrient rich bakery foods; nutrient rich traditional foods